Young people's attitudes towards Muslims in Sweden - Pieter Bevelander; Jonas Otterbeck (Institute for the Study of Labor (IZA), 2007)
Since the 1950's, the Muslim population in Sweden has grown from just a few individuals to approximately 350,000 of which one third is of school age or younger. With the use of multiple regression technique, the principal objective of this study has been to clarify and examine young people's attitudes towards Muslims, and the relationships between these attitudes and a large number of background factors. The material employed in the analysis comprises a representative sample of 9,498 non-Muslim youths (4,680 girls and 4,818 boys) between 1519 years of age. The main results of the study show that when controlling for several background variables simultaneously, many variables affect the attitude towards Muslims. The country of birth, socio-economic background and school/program factors are found to have an effect on the attitude towards Muslims. Moreover, especially socio-psychological factors, the relationship to friends and the perceptions of gender role patterns are found to be important. In addition, local/regional factors like high levels of unemployment, high shares of immigrants in a local environment also have an effect on the attitude towards Muslims. No differences in the attitude of boys and girls were measured. The article gives some support for the contact hypothesis and hypotheses on different kinds of social dominance. Finally, the influence of negative discourses on Islam and Muslims are discussed.
Keywords: 330; Islam; Migranten; Jugendliche; Meinung; Sozialpsychologie; Schweden